Fungsi Kalimat Interogatif pada Al-Qur’an Surat Muhammad : Dalam Perspektif Pendidikan Karakter - Alpan Noor Habib Rangkuti; Rinaldi Supriadi; Yayan Nurbayan (Universitas Nahdlatul Wathan Mataram, 2024)
The linguistic richness of the Al-Qur'an makes semantic studies very significantly dominant so that readers are able to obtain the meaning and the point of the sentence. This study aimed to analyze the function of interrogative sentences hidden in each interrogative sentence in Surah Muhammad, which is focusing on this implications for education. This research used a qualitative approach content analysis method. The results of the study showed that each interrogative sentence contained in surah Muhammad has various non-literal meanings, thus affecting the implication in education to be different. This research used a qualitative approach content analysis method. In the perspective of education, the function of interrogative sentences can be interpreted as a way of extracting the implied meaning such as the laws and strategies taught by Allah swt. through the Al-Qur’an so that those rules can be applied in real-life situation and become a place for self-reflection to improve the quality of life so that life will be more meaningful and become an example in behavior. Speaking of education is a national investment that must always undergo continuous renewal and improvement with the global demands that provide increasingly complex challenges. The most fundamental sources of education are the Al-Qur’an and sunnah.